The Effect Of Sanitary Pads Use On The Incidence Of Pruritus Vulva In Students Of Prima Indonesia University - Salsabila Armenia Margolang; Lisdawaty Siregar; Ade Arhamni Sumantri (Jurnal Ners, 2025)
Menstruation is a physiological process, but improper use of sanitary pads and poor vulvar hygiene can cause health problems such as vulvar pruritus. This study aimed to determine the frequency of sanitary pad replacement, the effect of disposable sanitary pad use on the incidence of vulvar pruritus, and vulvar hygiene behavior among female students at Prima University, Medan. This study used an analytical observational design with a cross-sectional approach involving 68 female medical students from the 2022 cohort selected through purposive sampling. Data were collected using a questionnaire and analyzed using the Chi-Square test. The results showed that most female students used disposable sanitary pads and the majority experienced mild vulvar pruritus. Data analysis found a statistically significant relationship between the type of sanitary napkin, frequency of replacement, cleanliness of use, and duration of sanitary napkin use with the incidence of vulvar pruritus. It was concluded that sanitary napkin use practices and vulvar hygiene behaviors strongly influence the incidence of vulvar pruritus in female students. It is hoped that female students can better maintain genital hygiene and replace sanitary napkins.